Pembelajaran Nahwu Dasar Tingkat Diniyah Asrama Man I Jember - Zainuri, Zainuri; Mannan, Ahmad Mizan Rosyadi Abdul Jalil; Wahyudi, Imam; Bukhori, Imam; Aminullah, Aminullah (INAIFAS Press, 2024)
The research results show that mentoring is proven to increase students' understanding of the material, increase interest in learning, and help students overcome difficulties in understanding complex terms and rules. Accompanying teachers play an important role in simplifying material, motivating students, and providing support and solutions to various problems faced by students during the learning process. In addition, effective mentoring strategies, such as the use of visual illustrations, practice questions, and discussions, have been proven to accelerate student understanding. This research concludes that assisting basic nahwu learning with a gradual approach can create a conducive learning environment, so that students can master nahwu rules more easily and confidently